2000
DOI: 10.1093/emboj/19.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of c-myc expression by IFN-γ through Stat1-dependent and -independent pathways

Abstract: Interferons (IFNs) inhibit cell growth in a Stat1-dependent fashion that involves regulation of c-myc expression. IFN-gamma suppresses c-myc in wild-type mouse embryo fibroblasts, but not in Stat1-null cells, where IFNs induce c-myc mRNA rapidly and transiently, thus revealing a novel signaling pathway. Both tyrosine and serine phosphorylation of Stat1 are required for suppression. Induced expression of c-myc is likely to contribute to the proliferation of Stat1-null cells in response to IFNs. IFNs also suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
233
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(244 citation statements)
references
References 86 publications
(147 reference statements)
9
233
0
2
Order By: Relevance
“…Studies employing wild type and Stat-1-null mouse embryonic fibroblasts identified a GAS element in the c-myc promoter that was necessary, but not sufficient, to suppress c-myc expression in wild-type cells. 22 Although a consensus exists that type I IFNs induce posttranscriptional modulation of c-myc mRNA, the molecular mechanism underlying this process is unclear. Different components of IFN-inducible RNA degradation machinery have been implicated in this action.…”
Section: Discussionmentioning
confidence: 99%
“…Studies employing wild type and Stat-1-null mouse embryonic fibroblasts identified a GAS element in the c-myc promoter that was necessary, but not sufficient, to suppress c-myc expression in wild-type cells. 22 Although a consensus exists that type I IFNs induce posttranscriptional modulation of c-myc mRNA, the molecular mechanism underlying this process is unclear. Different components of IFN-inducible RNA degradation machinery have been implicated in this action.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IFN-g induced cellular proteins, such as Stat-1, which could result in reduced expression of transgene. 17,30,31 Another study raised the possibility that IFN-g decreases the stability of several transcripts, including c-myc, c-fos and cftr. 18 However, such events would not be involved in the Mug-mediated suppression of transgene expression in the present study, because a single hydrodynamic injection of pCpGMug results in a sustained level of Mug in mouse serum, indicating that the transgene expression from pCpG-Mug is not suppressed by Mug.…”
Section: Inhibition Of Transgene Expression By Ifn-c L Zang Et Almentioning
confidence: 99%
“…For example, IFN-α can reduce c-myc mRNA stability in Daudi cells [48,49] but increases c-myc mRNA in murine fibroblasts [50]; IFN-β serine 17 can also inhibit cmyc mRNA stability in a colon carcinoma cell line [51]. While it is known that c-myc gene expression is decreased by IFN-γ in a Stat1-dependent manner in embryonic mouse fibroblasts [52], IFN-γ increases c-myc mRNA stability in a human breast cancer cell line [53]. Thus, IFNs have contra-indicatory roles on stability of c-myc mRNA, a transcriptional factor that regulates cell proliferation, and the response seems to be dependent on both of the type of IFN and the target cell.…”
Section: Role Of Ifn In Post-transcriptional Control Of Cellular Genementioning
confidence: 99%